Pengaruh Kepemilikan Institusional, Kepemilikan Manajerial dan Komite Audit terhadap Pengungkapan CSR pada Perusahaan Manufaktur - Afriyanti, Anita; Luhgiatno, Luhgiatno - (STIE PENA, 2024)
This research aims to analyze the influence of institutional ownership, managerial ownership and audit committee on CSR disclosure. The independent variables used in this research are institutional ownership, managerial ownership, and audit committee. The dependent variable in this research is expanding CSR. This research uses secondary data originating from annual financial reports. The population in this research are manufacturing companies in the goods and consumption sector listed on the Indonesia Stock Exchange for the 2019-2022 period. The sampling technique used was purposive sampling and the total sample was 23 companies. The analysis method uses the SPSS 25 program. The results of this research show that institutional ownership and managerial ownership have a significant negative effect on CSR disclosure, while the audit committee does not have a significant effect on CSR disclosure. Keywords: Profitability, Liquidity, Company Size, and Company Value.